Interlaminar fracture toughness of aerospace-grade carbon fibre reinforced plastics interleaved with thermoplastic veils. (January 2020) - Quan, Dong; Bologna, Francesca; Scarselli, Gennaro; Ivankovic, Alojz; Murphy, Neal
Abstract: This work investigates the toughening performance of thermoplastic veils when used to interlay aerospace-grade CFRPs. Veils based on Polyethylene-terephthalate (PET), Polyphenylene-sulfide (PPS) and Polyamide-12 (PA) fibres ( 10 μ m in diameter) were used as interlayers of unidirectional (UD), non-crimp fabric (NCF) and 5-Harness satin weave (5H) carbon fibre/epoxy laminates. During a hot curing process of the laminates, the PET and PPS veils remained in a fibrous form, and the PA veils melted. This resulted in different toughening mechanisms, i.e. interlaying the PET and PPS veils introduced extensive thermoplastic fibre bridging, and adding the PA veils improved the fracture toughness of the epoxy matrix. The different toughening mechanisms of the veils, together with the different fracture mechanisms of the laminates, dramatically affected the toughening levels. In general, the PET and PPS veils were more effective for toughening the UD laminates, and the PA veils were superior for the NCF and 5H laminates.